INTENSITAS SERANGAN DAN PERSENTASE KERUSAKAN TANAMAN JERUK TERSERANG CVPD (Citrus Vein Phloem Degeneration) DI KABUPATEN KARANGASEM - I Made Asta Gunawan; I Gusti Ayu Diah Yuniti; Putu Lasmi Yuliyanthi Sapanca (Faculty of Agriculture and Business, Universitas Mahasaraswati Denpasar , Kec. Denpasar Utara, Kota Denpasar, Bali 80233, 2024)
Citrus are a local fruit that is widely available on the market. The quality of citrus fruit can be influenced by various factors, including attacks by Citrus Vein Phloem Degeneration (CVPD). CVPD is a disease of citrus plants, known as citrus greening, yellow shoot, leaf mottle (Philippines), likubin or decline (Taiwan), citrus dieback (India), blotchy-mottle or mottling disease (Africa); with the international name huanglongbing (China). CVPD disease is classified as one of the important diseases in citrus plants which has developed widely and is the main obstacle to efforts to develop and increase orange production in Bali. PCR analysis to detect the presence of CVPD disease is carried out using specific primers from 16S rDNA. Based on the results of observing symptoms in Karangasem Regency, the percentage of damage due to CVPD ranges from 61% to 87%. The average percentage of citrus plants showing symptoms of CVPD attack was 72.67%, the lowest percentage was experienced by tangerines and the highest was shown by Selayar oranges (87%).